Duffy Red Cell Antigen Phenotype among Indigenous Pregnant Women attending Antenatal Clinic at Federal Teaching Hospital Gombe, Gombe State, North Eastern Nigeria - Ahmed M. Gaji; Ann Ogbenna; Ahmed I. Girei; Kasim M. Pindiga; Sani Adamu; Saleh Yuguda; Ademola Adewoyin; Davies Nosimot Omotola (International Journal of Blood Transfusion, 2023)
Background and Objectives Duffy (FY) blood group system is implicated in transfusion incompatibilities and haemolytic disease of the foetus and newborn (HDFN). The primary objective was to determine the Duffy phenotype among indigenous pregnant women in Gombe, Gombe State, Nigeria. Materials and Methods This was a Cross sectional study where simple random sampling was employed on consented participants. Two hundred and fifty nine pregnant women attending antenatal clinic at Federal Teaching Hospital Gombe were randomly recruited into the study. About 3mls of blood was taken, and Duffy antigen typed by standard tube technique (LORNE LABORATORY UK). Results Among the Indigenous tribe, the percentage of Fy(a+b+) was seen in 2.2% of Fulani and 3.4% of Tangale, Fy(a+b-) phenotype was seen in 4.3% of Tangale, 6.8% of Fulani,9.5% of Tera, 10.3% of Hausa and 10.5% of Waja. Fy(a-b+) phenotype was seen in 5.3% of Waja, 7.6% of Fulani,8.7% of Tangale, 9.5% of Tera and 12.5% of Bolawa. Fy(a-b-) phenotype was seen in 2.4% of Tula,6.4% of Bolawa,7.3% of Waja, 7.8% of Tera, 17.8% of Tangale, 11.8% of Hausa and 46.5% of Fulani. About 84.6% of the study population had the null Duffy phenotype. Conclusion The research showed the phenotypic distribution of Duffy blood group among the study participants with relatively high percentage of null Duffy phenotype hence possible risk of alloimmunisation.
Keywords: Duffy Phenotype